The United Nations and decolonization
1 online resource (viii, 244 pages).
Keywords: "Differing interpretations of the early history of the United Nations on the one hand conceive it as an instrument to promote colonial interests while on the other emphasizing its influence in providing self-determination for dependent territories. The authors in this book explore this dynamic in order to increase our understanding of both the achievements and the limits of international support for the independence of colonized peoples. This book will prove foundational for scholars and students of modern history, international history and postcolonial history"--